Financial literacy as an important aspect in the area of business sustainability: the case of Slovak Republic - Kicová, Eva; Poniščiaková, Oľga; Rosnerová, Zuzana; Fabuš, Juraj (Business: Theory and Practice, 2024)
The essence of literacy is currently understood on a broader level. Emphasis is placed on functional literacy, which also includes financial literacy. Its level significantly affects a person’s standard of living. In the contribution, we are devoted to the investigation of this issue and the possibilities of increasing the level of financial literacy in the Slovak Republic. We will use theoretical and empirical scientific methods. We work with analysis, synthesis, induction, and deduction. Subsequently, empirical scientific techniques that work with concrete data and precise methods to achieve results will be used. In addition to explanatory methods, interpretative methods will also be used. According to the level of financial literacy of respondents based on the interview method, hypotheses are established. An analysis of individual answers and an analysis of the impact of financial literacy on young people’s interest in entrepreneurship will be carried out. The findings led to the definition of practically oriented conclusions, with an emphasis on the assessment of the level of financial literacy. Attention is also paid to incentives for young entrepreneurs. All proposals written in this chapter are designed with the intention of improving the level of financial literacy in Slovakia.